Isolation and Antimicrobial Resistance Patterns of Aeromonas hydrophila from Diarrheal children in Thi-Qar Province/Iraq - K. Hanan , Zaman (University of Thi-Qar Journal of Science, 2019)
This study was carried out to isolate Aeromonas hydrophila from diarrheal children; 150 fecal samples were collected from diarrheal children with age (1-13 years) of both sexes that had suffering from diarrhea in Mohammed Al -Mosawi and Bent-Al-Huda hospitals in Thi-Qar province. Twenty isolates were diagnosed as genus Aeromonas hydrophila. The results revealed that the rate of Aeromonas hydrophila isolates in fecal samples of diarrheal children was (13.3%) and the age groups of 1-5 years were the highest percentage of diarrheal cases (60%) and the highest percentage of Aeromonas hydrophila infection (40%). Antimicrobial susceptibility testing to 20 Aeromonas hydrophila isolates showed that (70%) of isolates were resistance to Amikacin, while (60%) of isolates were resistance to Ciprofloxian, Cefotaxime and Gentamycin ,(35%) of isolates were resistance to Ceflazim and only (20%) of isolates were resistance to Imipenem, and the results appeared increasing prevalence of multidrug resistant between Aeromonas hydrophila isolates that isolated from diarrheal children in Thi-Qar province.